Kebijakan standar Ganda International Atomic Energy Agency (IAEA) Dalam Menyelesaikan Kasus Nuklir Iran Dan Israel - Muhammad Aminudin Fatah; Soelistyati Ismail Gani (Jurnal Studi Diplomasi dan Keamanan, 2015)
Iran and Israel nuclear programs that began to lead to military purposes has caused anxiousness for other countries. These issues push International Atomic Energy Agency (IAEA) as an international body in charge of supervising in the nuclear field to take policy related to nuclear technology in both countries. However, the policies that have applied by IAEA have double standards in resolving both cases. This thesis aims to explain why IAEA apply double standards policies in resolving the nuclear case of Iran and Israel. This study uses the theory of intergovernmentalism and neo-institutional approach to explain the factors that influence those policies. Through the analysis approach, emerge an hypothesis that position of the United States as dominant actor in the IAEA policy-making process and the existence of other actor’s actions which affect the legal status of the nuclear program safeguard impacted to IAEA double standard policies.